Performance evaluation of Brands' digital cash system in TCP/IP environment - Teo, Pock Chueng; Sha`ameri, Ahmad Zuri; Ashourian, Mohsen (2003)
Brands' digital cash system is a single term system that builds on two concepts, Schnorr digital signature and the representation problem in group of prime order. The Brands' scheme is almost as efficient as the fully traceable offline systems. In this paper, we evaluate the performance of Brands' system in TCP/IP Environment and report the results in various conditions.